Seed Functional Traits Provide Support for Ecological Restoration and ex situ Conservation in the Threatened Amazon Ironstone Outcrop Flora - Zanetti, Marcilio; Dayrell, Roberta L. C.; Wardil, Mariana V.; Damasceno, Alexandre; Fernandes, Tais; Castilho, Alexandre; Santos, Fernando M. G.; Silveira, Fernando A. O. (Frontiers in Plant Science, 2020)
Cangas (ironstone outcrops) host a specialized flora, characterized by high degree of edaphic endemism and an apparent lack of natural history knowledge of its flora. Due to intense pressure from iron ore mining this ecosystem is under threat and in need of restoration. We studied seed functional traits that are relevant for restoration, translocation and ex situ conservation in 48 species from cangas in eastern Amazon. Were determined the thermal niche breadth, classified seed dormancy and determined methods to overcome it, determined the effect of seed storage on germination, tested the association between germination traits and functional groups, and tested whether seed traits are phylogenetically conserved. We found a broad interspecific variation in most seed traits, except for seed water content. Large interspecific variation in the temperature niche breadth was found among the studied species, but only four species, showed optimum germination at high temperatures of 35°C to 40°C, despite high temperatures under natural conditions. Approximately 35% of the studied species produced dormant seeds. Mechanical scarification was effective in overcoming physical dormancy and application of gibberellic acid was effective in overcoming physiological dormancy in five species. For the 29 species that seeds were stored for 24 months, 76% showed decreases in the germination percentage. The weak association between germination traits and life-history traits indicate that no particular plant functional type requires specific methods for seed-based translocations. Exceptions were the lianas which showed relatively larger seeds compared to the other growth-forms. Dormancy was the only trait strongly related to phylogeny, suggesting that phylogenetic relatedness may not be a good predictor of regeneration from seeds in cangas. Our study provides support to better manage seed sourcing, use, storage and enhancement techniques with expected reduced costs and increased seedling establishment success.